2003
DOI: 10.1021/np020393a
|View full text |Cite
|
Sign up to set email alerts
|

Rigidins B−D, New Pyrrolopyrimidine Alkaloids from a Tunicate Cystodytes Species

Abstract: Three new pyrrolopyrimidine alkaloids, rigidins B-D (1-3), have been isolated from an Okinawan marine tunicate Cystodytes sp., and the structures were elucidated on the basis of spectroscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…10-12 The first general total synthesis of rigidins A, B, C and D, which involved only four steps from commercially available materials, was reported by the authors in 2011 13 and allowed for a thorough investigation of their biological properties. However, despite the earlier reports of promising antiproliferative activity against murine leukemia L1210 cells, 11 the rigidins were found to have very little, if any, activity against cultured human cancer cells. 14 Further synthetic investigations led to the development of approaches allowing for the modification of the 7-deazaxanthine skeleton present in the rigidins to obtain the corresponding 7-deazahypoxanthine ( A ), 7-deazaadenine ( B ) and 7-deazapurine ( C ) frameworks (Figure 1).…”
Section: Introductionmentioning
confidence: 77%
“…10-12 The first general total synthesis of rigidins A, B, C and D, which involved only four steps from commercially available materials, was reported by the authors in 2011 13 and allowed for a thorough investigation of their biological properties. However, despite the earlier reports of promising antiproliferative activity against murine leukemia L1210 cells, 11 the rigidins were found to have very little, if any, activity against cultured human cancer cells. 14 Further synthetic investigations led to the development of approaches allowing for the modification of the 7-deazaxanthine skeleton present in the rigidins to obtain the corresponding 7-deazahypoxanthine ( A ), 7-deazaadenine ( B ) and 7-deazapurine ( C ) frameworks (Figure 1).…”
Section: Introductionmentioning
confidence: 77%
“…Preliminary biological results showed that at 10 μg/mL, compounds 4–6 inhibited leukemia tumor cell growth by 40%, 40% and 20% respectively [11]. …”
Section: Resultsmentioning
confidence: 99%
“…This compound exhibited antagonistic activity against calmodulin. The biological activities of the related compounds, rigidin B ( 29 ), C ( 30 ) and D ( 31 ), which were isolated from a different species of tunicate, Cystodytes sp., are yet to be determined [34]. …”
Section: Simple Dehydrotyrosine Derivatives: Tuberine Erbastatinmentioning
confidence: 99%